Nghiên cứu ảnh hưởng của thời gian nung đến quá trình tổng hợp dung dịch rắn GaN – ZnO - Vo Vien; Nguyen Van Kim; Nguyen Thi Viet Nga; Nguyen Tien Trung; Le Truong Giang; Pham Huy Hanh; Luc Huy Hoang; Sung-Jin Kim (My University, 2016)
Nghiên cứu ảnh hưởng của thời gian nung đến quá trình tổng hợp dung dịch rắn GaN – ZnO
Keywords: Thời gian nung